(untitled) (Journal of Organizational Psychology, 2021)
The study of reciprocity within inter-organizational exchanges has been a widely investigated subject matter since the concept was first declared a universal personal norm by Gouldner (1960). In business practice, many networking organizations thrive on creating an environment where professionals can pass leads, referrals, and clients to one another for mutual gain (BNI, 2017). Though the power of professional reciprocity is actualized in industry, this study seeks to identify specific factors that influence a professional’s sentiment of reciprocity. This quantitative research investigates influencers both on the positive (rewarding) and negative (punishing) sides of the reciprocity spectrum. Study findings identified that industry type, professional experience, and gender act as factors that directly act as influencers of negative reciprocity. In contrast, a professional’s education level is shown to influence positive reciprocity directly. These findings have aided in creating the Reciprocal Influencers Model and posits that professional reciprocity should also be considered a universal business norm.